Relevance of the Educational Evaluation System to Strengthening Students’ Digital Literacy and Character - Muhamad Yani; Abdul Fattah; Suhirman Suhirman; Fatturahamn Muhtar (International Journal of Technology and Education Research, 2026)
This study aims to analyze the relevance of educational evaluation systems to strengthening students’ digital literacy and character in the context of contemporary education. The study is motivated by educational transformation in the digital era, which requires evaluation systems to focus not only on academic achievement but also on strengthening 21st-century competencies and students’ character development. The research employed a qualitative approach using the library research method. Data were collected through documentation studies of national and international scientific articles, academic books, and relevant educational documents published between 2021 and 2026. Data collection techniques included literature review, data reduction, theme classification, and content analysis. Data analysis employed the interactive model of Miles and Huberman as well as thematic analysis to identify major research patterns and themes. The findings reveal that digital- and authentic-based educational evaluation significantly contributes to strengthening digital literacy, critical thinking abilities, social responsibility, and students’ character development. Evaluations based on projects, digital portfolios, and self-reflection are capable of fostering digital ethical awareness and increasing students’ active participation in learning. However, the implementation of contemporary educational evaluation still faces challenges related to limited teacher digital competence, technological infrastructure, and evaluation cultures that remain focused primarily on academic achievement. This study contributes to the development of competency-based educational evaluation concepts that are more holistic, adaptive, and humanistic.